PERIOPERATIVE DIABETIC KETOACIDOSIS ASSOCIATED WITH SODIUM-GLUCOSE CO-TRANSPORTER-2 INHIBITORS : A SYSTEMATIC REVIEW - Anggi Manurung, Hananya Dwi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
DKA or diabetic ketoacidosis is an emergency condition caused by hyperglycemia in which excessive acid is produced in the blood. Patients with type 1 and type 2 diabetes who undergo surgery, have an infection, or are under extreme stress can also develop DKA. The body generates the hormone adrenaline to combat infection and stress, but this can have a negative effect on blood glucose levels (adrenaline is counterinsulin). This can worsen if the patient refuses to take diabetes medication or inject insulin during stressful or infectious situations. The fundamental components of the pathophysiological mechanisms at play in diabetic ketoacidosis (DKA) include shifts in hormone levels and the ensuing inflammatory response. Alterations in the concentration of hormones lead to shifts in the production and consumption of glucose, as well as an increase in lipolysis and the formation of ketone bodies. Canagliflozin, dapagliflozin, empagliflozin, and ertugliflozin are agents approved by the Food and Drug Administration (FDA) for the treatment of type 2 diabetes mellitus (DM) in adults. Acting on proteins, the four agents are SGLT2 inhibitor class agents. SGLT-2 is expressed in the kidney's proximal tubule. This may result in a decrease in filtered glucose reabsorption, a decrease in the renal threshold for glucose (RTG), and an increase in glucose excretion via urine. Diabetes patients treated with sodium–glucose transport protein 2 (SGLT2) inhibitors have also been reported to experience DKA. The results of a study indicate that DKA is uncommon among T2DM patients treated with SGLT2 inhibitors.